2023
DOI: 10.3390/cancers15194756
|View full text |Cite
|
Sign up to set email alerts
|

DKK1 Promotes Epithelial–Mesenchymal Transition and Cisplatin Resistance in Gastric Cancer via Activation of the PI3K/AKT Pathway

Jian Li,
Yaqiong Zhang,
Fangzhou Ye
et al.

Abstract: Chemotherapy is a classical method of cancer treatment. Cisplatin-based chemotherapy is a traditional and essential therapeutic approach in gastric cancer treatment. However, the development of drug resistance during treatment is a major obstacle that limits their further application, and molecular changes have occurred in the development of drug resistance. Here, we found that Dickkopf-related protein 1 (DKK1) is highly expressed in gastric cancer and related to poor prognosis in gastric cancer patients throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…Interestingly, we have found that higher concentrations of some OCPs, PCBs as well as ΣPOPs were positively correlated with the gene expression of a variety of promoters related to these signaling pathways such as PDGFRα, HMGA1, HOXA10, CCR1, FOXM1 or FUT8 genes. A similar trend was observed for DKK1, though the available evidence attributes a dual role to DKK1 during the EMT process [57,58]. These results are in line with previous studies suggesting up-regulation of PDGFRα gene expression in estrogen-dependent cells, such as epithelial mammary cells exposed to a pesticide mixture [83].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Interestingly, we have found that higher concentrations of some OCPs, PCBs as well as ΣPOPs were positively correlated with the gene expression of a variety of promoters related to these signaling pathways such as PDGFRα, HMGA1, HOXA10, CCR1, FOXM1 or FUT8 genes. A similar trend was observed for DKK1, though the available evidence attributes a dual role to DKK1 during the EMT process [57,58]. These results are in line with previous studies suggesting up-regulation of PDGFRα gene expression in estrogen-dependent cells, such as epithelial mammary cells exposed to a pesticide mixture [83].…”
Section: Discussionsupporting
confidence: 90%
“…For instance, HMGA1, FOXM1, RXRA, FUT-8, POU5F1, or HOXA10 gene products promote EMT, while DUSP6 and AGR2 gene products decreased EMT via the TGF-β signaling pathway [49][50][51][52][53][54][55][56]. Similarly, DDK1, CDK1, or SOX2 and CCR1 or CHUK have been shown to regulate Wnt-driven and Notch/NF-κB-driven EMT, respectively [57][58][59][60][61][62]. Other soluble factors, such as the RRM2 gene product, promote EMT by targeting JAK2/STAT3 intracellular cascade [63].…”
Section: Introductionmentioning
confidence: 99%